2014
DOI: 10.1152/ajprenal.00058.2014
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase-derived reactive oxygen species contribute to impaired cutaneous microvascular function in chronic kidney disease

Abstract: Oxidative stress promotes vascular dysfunction in chronic kidney disease (CKD). We utilized the cutaneous circulation to test the hypothesis that reactive oxygen species derived from NADPH oxidase and xanthine oxidase impair nitric oxide (NO)-dependent cutaneous vasodilation in CKD. Twenty subjects, 10 stage 3 and 4 patients with CKD (61 ± 4 yr; 5 men/5 women; eGFR: 39 ± 4 ml·min(-1)·1.73 m(-2)) and 10 healthy controls (55 ± 2 yr; 4 men/6 women; eGFR: >60 ml·min(-1)·1.73 m(-2)) were instrumented with 4 intrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 83 publications
5
44
1
Order By: Relevance
“…29, 30 In addition, apocynin perfusion through microdialysis probes has previously been found to blunt local angiotensin II-mediated vasoconstriction in the human cutaneous microvasculature, 31 and to restore local cutaneous vascular conductance in chronic kidney disease patients. 32 Thus, the findings in the present study that apocynin delivery via microdialysis augments local microvascular function are not without precedent. Conversely, apocynin incubation has been shown to have no effect on flow-induced dilation in coronary resistance arteries from cardiopulmonary bypass patients.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…29, 30 In addition, apocynin perfusion through microdialysis probes has previously been found to blunt local angiotensin II-mediated vasoconstriction in the human cutaneous microvasculature, 31 and to restore local cutaneous vascular conductance in chronic kidney disease patients. 32 Thus, the findings in the present study that apocynin delivery via microdialysis augments local microvascular function are not without precedent. Conversely, apocynin incubation has been shown to have no effect on flow-induced dilation in coronary resistance arteries from cardiopulmonary bypass patients.…”
Section: Discussionmentioning
confidence: 54%
“…The marked inhibition of ROS by apocynin strongly suggests that apocynin does not have a pro-oxidant effect in this system. Despite the potential limitations of apocynin, it is by far the most commonly used Nox inhibitor available 31,32,35,37,40 , and at the concentrations employed by use in these studies, it is unrealistic to expect that any potential antioxidant effect of this compound could explain the effects observed here. A few subjects from each group dropped out of the exercise program prior to completion, thus data was not attained from these subjects for post-training measures.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, impaired cutaneous microvascular function leading to attenuated vasodilation has been linked to attenuated NO bioavailability associated with elevated ROS, as decreasing O 2 − through the local administration of tempol, a SOD mimetic, restored cutaneous vasodilation in young smokers and patients with chronic kidney disease [133]. Moreover, inhibition of NADPH oxidase (apocynin) restored cutaneous vasodilation in the chronic kidney disease patients, suggesting an important role of this free radical producing enzymatic complex in the production of O 2 − [134]. Additionally, acute Vitamin C supplementation, alone or in combination with arginase, improved reflex cutaneous vasodilation during whole body heating in both older [135] and hypertensive [136] individuals.…”
Section: Free Radical Regulation Of Skin Blood Flowmentioning
confidence: 99%
“…To the contrary, we found that CKD was associated with a lower prevalence of VMS in this cohort. We speculate that pre-existing vascular disease among women with CKD including vascular calcification, arterial stiffness and impaired endothelial function 33,34 might interfere with vasodilation required to expel heat in VMS. Alternatively, the lower prevalence of VMS among women with CKD may be related to lower body temperature 35,36 in patients with CKD or alterations in the hypothalamic-pituitary axis.…”
Section: Discussionmentioning
confidence: 99%